2020
DOI: 10.3390/ijgi9020112
|View full text |Cite
|
Sign up to set email alerts
|

Smart Tour Route Planning Algorithm Based on Naïve Bayes Interest Data Mining Machine Learning

Abstract: A smart tour route planning algorithm based on a Naïve Bayes interest data mining machine learning is brought forward in the paper, according to the problems of current tour route planning methods. A machine learning model of Naïve Bayes interest data mining is set up by learning a mass of training data on tourists’ interests and needs. Through the recommended interest tourist site classifications from the machine learning module, the optimal tourist site mining algorithm based on the membership degree searchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Also, taking into account the connectedness between the text mining technique (e.g., sentiment analysis) and machine learning or classification models (Ofli et al, 2016 ), the study of Dey et al ( 2016 ) notes that the sentiments which are often found in the comments or feedbacks (e.g., SET) can be categorized by polarity (i.e., positive, neutral, or negative Kalaivani, 2013 ; Litman & Forbes-Riley, 2004 ; Okoye et al, 2020 ), and then utilized to provide valuable pointers or indicators in connection to the various reasons or purposes for which the datasets are analyzed (e.g., the advances in teaching analytical methods and/or students’ evaluation of teaching described in this study). Besides, the authors (Dey et al, 2016 ) also used a statistical method that supports the K-nearest neighbour (KNN) (Abu Alfeilat et al, 2019 ; Ghosh et al, 2020 ; Viji et al, 2020 ) and Naïve Bayes’(Zhou et al, 2020 ) supervised machine learning algorithms to capture the different words/sentence polarities and elements of the subjective styles or patterns.…”
Section: Background Informationmentioning
confidence: 99%
“…Also, taking into account the connectedness between the text mining technique (e.g., sentiment analysis) and machine learning or classification models (Ofli et al, 2016 ), the study of Dey et al ( 2016 ) notes that the sentiments which are often found in the comments or feedbacks (e.g., SET) can be categorized by polarity (i.e., positive, neutral, or negative Kalaivani, 2013 ; Litman & Forbes-Riley, 2004 ; Okoye et al, 2020 ), and then utilized to provide valuable pointers or indicators in connection to the various reasons or purposes for which the datasets are analyzed (e.g., the advances in teaching analytical methods and/or students’ evaluation of teaching described in this study). Besides, the authors (Dey et al, 2016 ) also used a statistical method that supports the K-nearest neighbour (KNN) (Abu Alfeilat et al, 2019 ; Ghosh et al, 2020 ; Viji et al, 2020 ) and Naïve Bayes’(Zhou et al, 2020 ) supervised machine learning algorithms to capture the different words/sentence polarities and elements of the subjective styles or patterns.…”
Section: Background Informationmentioning
confidence: 99%
“…Ding et al [31] and zhang et al [32] used an improved neural network for POI recommendation. Based on naïve Bayes interest data mining machine learning, a smart tour route planning algorithm was proposed by Zhou et al [1]. In addition, there are other studies on POI and route recommendations [33][34][35][36][37][38][39].…”
Section: Related Workmentioning
confidence: 99%
“…, p ijk ), which are the candidate points. The projection proj(p ij , r j ) of point p ij onto r j : proj p ij , r j = arg min ed p ij , p ijk p ijk ∈r j (1) where ed(p ij , p ijk ) are the Euclidean distances between a POI and its projected points on the adjacent road segments.…”
Section: Pois To Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional sightseeing route planning, the landscape architects or planners usually provide differently themed sightseeing routes according to the special categories of scenic spots-for example, natural, cultural, aesthetic, and recreational spots, are the main focus [8]. This kind of method focuses on a landscape's features rather than the tourists' needs and interests [9]. Moreover, for a diversified demand of visiting time, tourism guides also provide the sightseeing routes classified by the expected consumed time, such as a Table 1.…”
Section: Introductionmentioning
confidence: 99%